MISPRONUNCIATION MADE BY FRESHMEN OF UNIVERSITAS KLABAT - Rondonuwu, Joppi J (JIU (Jurnal Ilmiah Unklab); Volume 5 No. 1, 2002 JIU UNKLAB, 2002)
This classroom observation a number of English words commonly mispronounced by 132 freshmen at Universitas Klabat. The researcher found out that quite a number of students were not able to demonstrate correct pronunciation, in spite of repeated drills and practices facilitated in the classroom and English laboratory. They had difficulty pronouncing (1) the verbs and nouns ending in – s, of both hissing and non-hissing sounds; (2) the suffix – ed that is added to verbs ending in /t/ or /d/; (3) short /o/ sound that spelled /au/ in front of a consonant; (4) words with /ea/ component; (5) sh-component; and (6) the sound of short /uh/ spelled oo.